Long-Term Prevalence of Disaster-Related Deep Vein Thrombosis in Minamiaso Village After the 2016 Kumamoto Earthquakes: A Prospective Cross-Sectional Analysis. (19th October 2022) - Onishi, Hidenori; Yamamura, Osamu; Tsubouchi, Hiromasa; Hirobe, Takeshi; Kosugi, Ikuko; Enomoto, Soichi; Yamamoto, Tami; Daitoku, Satoshi; Satou, Naomi; Chiba, Hiroshi; Kai, Yutaka; Hashimoto, Yoichiro; et al.
Abstract: Objective: This study aimed to examine the prevalence of deep vein thrombosis (DVT) among evacuees in Minamiaso, a village which was temporarily isolated after the earthquakes, from the acute to recovery phase after the 2016 Kumamoto Earthquakes (GLIDE no: EQ-2016-000033-JPN). Methods: This prospective study, which was approved by Fukui University Medical Research Ethics Committee (approval no. 20160024 and 20160089), enrolled 181 evacuees (73.9 ± 11.6 y) who participated in a series of 3 DVT screenings using portable ultrasound machines conducted over 19 mo. All participants completed a questionnaire before the screenings, and none of the participants attended all 3 screenings. Data analysis was performed using EZR version 1.41. Results: The DVT prevalence was 14.3% (79.4 ± 8.2 y) at first screening of evacuees staying in shelters and 18.5% (71.5 ± 13.1 y) and 12.2% (72.8 ± 10.9 y) in second and third screenings of evacuees staying in temporary housing, respectively. Multivariate analysis revealed age ≥75 y and alcohol consumption as independent risk factors in the entire cohort and in patients aged ≤74 y, respectively. Conclusions: A high DVT prevalence over a long time period of 19 mo was observed where survivors were temporarily isolated after the disaster.